Genetic diversity and cross-species transmission of kobuviruses in Vietnam. Issue 1 (13th February 2018) - Lu, Lu; Van Dung, Nguyen; Ivens, Alasdair; Bogaardt, Carlijn; O'Toole, Aine; Bryant, Juliet E; Carrique-Mas, Juan; Van Cuong, Nguyen; Anh, Pham Hong; Rabaa, Maia A; Tue, Ngo Tri; Thwaites, Guy E; et al.
Abstract: Cross-species transmission of viruses poses a sustained threat to public health. Due to increased contact between humans and other animal species the possibility exists for cross-species transmissions and ensuing disease outbreaks. By using conventional PCR amplification and next generation sequencing, we obtained 130 partial or full genome kobuvirus sequences from humans in a sentinel cohort in Vietnam and various mammalian hosts including bats, rodents, pigs, cats, and civets. The evolution of kobuviruses in different hosts was analysed using Bayesian phylogenetic methods. We estimated and compared time of origin of kobuviruses in different host orders; we also examined the cross-species transmission of kobuviruses within the same host order and between different host orders. Our data provide new knowledge of rodent and bat kobuviruses, which are most closely related to human kobuviruses. The novel bat kobuviruses isolated from bat roosts in Southern Vietnam were genetically distinct from previously described bat kobuviruses, but closely related to kobuviruses found in rodents. We additionally found evidence of frequent cross-species transmissions of kobuviruses within rodents. Overall, our phylogenetic analyses reveal multiple cross-species transmissions both within and among mammalian species, which increases our understanding of kobuviruses genetic diversity and the complexity of their evolutionary history.